Penilaian Tingkah Laku Sapi Brahman Cross Selama Proses Loading dan Unloading - Aditia, E. L.; Priyanto, R.; Muhammad, A. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2018)
Loading and unloading process may lead stress to the animal. The stress can be observed from behavior action of the animal. The aim of the study was to assess behavior during loading and unloading process. Total 24 loading groups (LG) with 11 Brahman cross cattles for each LG was observed during study. An average bodyweight of the cattle was 521±28.14 kg. The data was analyzed descriptively with score, frequency and duration of each behavior action. The results showed that the cattle had loading time of S score (very bad) and behavior score 3 (average). Meanwhile the unloading time of T score (very good) and behavior score of 3 (average). Slips, jump, and fall behavior were the behavior that frequent occured during the loading and unloading process. In general, the loading process potentially stressful for cattle compare to unloading process.